Financial Inclusion In The Age Of Algorithmic Innovation: Exploring The Interplay Between Digital Finance, Behavioral Economics, And Economic Empowerment - Marvin Linus (CV. SINAR HOWUHOWU, 2025)
This study examines the evolving landscape of financial inclusion in an era increasingly shaped by algorithmic innovation, analyzing the interplay between digital finance, behavioral economics, and economic empowerment across diverse socio-economic contexts. As algorithm-driven platforms—from mobile banking and digital wallets to AI-based credit scoring become central to financial ecosystems, understanding their behavioral, distributive, and developmental implications is critical. Drawing on interdisciplinary theoretical frameworks and emerging empirical evidence, this research explores how digital financial services modify individual decision-making, reshape risk perceptions, and influence saving, borrowing, and spending behaviors. Findings suggest that algorithmic systems can significantly expand access to financial resources, reduce transaction costs, and enhance economic participation among marginalized populations. However, the study also identifies behavioral biases, digital literacy gaps, and algorithmic asymmetries that may reinforce exclusion or introduce new vulnerabilities, particularly in low-income and rural communities. By integrating behavioral insights with technological and institutional analysis, this research provides a comprehensive understanding of how algorithmic finance can both enable and constrain empowerment outcomes. The study concludes by highlighting policy strategies that optimize digital finance for equitable and sustainable economic inclusion.